Post‐Procedural Bivalirudin Infusion Following Primary PCI to Reduce Stent Thrombosis. (29th January 2016) - Kinnaird, Tim; Yazji, Khaled; Thornhill, Laurence; Butt, Mehmood; Ossei‐Gerning, Nicholas; Choudhury, Anirban; Mitra, Rito; Anderson, Richard
Abstract : Background: Prolonging infusions may abrogate the acute stent thrombosis (ST) associated with bivalirudin use during primary PCI but at an increased cost. We hypothesized that continuing the bivalirudin infusion commenced during the procedure at the PCI recommended dose until infusion end would prevent excess early ST. Methods: Baseline demographics, procedural data and outcomes were gathered prospectively on 1395 consecutive patients undergoing primary PCI. The choice of bivalirudin versus heparin was at the cardiologist's discretion. Local protocol recommended continuation of the procedural bivalirudin at the PCI dose until infusion end. Results: Patients' mean age was 62.8 ± 13.1years with 11.4% presenting with shock. The majority of patients underwent PCI using bivalirudin with fewer using heparin (87.7 vs. 12.3%, P < 0.0001). Glycoprotein inhibitor bailout rates were 6.1% with bivalirudin and 36.3% with heparin (P < 0.0001). Calculated on an individual patient basis the median intra‐procedure duration of the bivalirudin infusion was 30(IQR 21‐43) minutes and post‐procedure 49(32–66) minutes. The acute (<24‐hours) ST rates were 4/1224 with bivalirudin ± GPI (0.3%) and 0/171 with heparin ± GPI (0%, P = 0.41). The sub‐acute (24‐hours to 30‐days) ST rates were 3/1224 for bivalirudin ± GPI (0.3%) and 2/171 with heparin ± GPI (1.2%, P = 0.11). In total the early (<30‐days) ST rates were 7/1224 for bivalirudin ± GPI (0.6%) and 2/171 with heparin ± GPI (1.2%, P = 0.31). Acute ST was significantly more likely to occur in clopidogrel‐loaded patients than prasugrel/ticagrelor patients (2.7 vs. 0.5%, P = 0.003). Conclusion: Continuing the bivalirudin infusion commenced during the procedure at the PCI recommended dose until infusion end combined with potent P2 Y12 inhibitors ameliorates excess early stent thrombosis. (J Interven Cardiol 2016;29:129–136)